Nueva fusayola con inscripción en signario celtibérico de la necrópolis vaccea de Las Ruedas de Pintia (Padilla de Duero-Peñafiel, Valladolid) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2019)
First study of a short inscription in Celtiberian characters on a spindle whorl found in a pit at Las Ruedas, the necropolis belonging to the Vaccean town of Pintia. Dated between the last third of the 2nd c. and the first half of the 1st c. BC, its text seems to read Te. Ke. be. Ka. A. To. Ko. Ta. Tu. The following interpretation deke Beka, A(n)doko datu ‘accipe, o Baebaca; Andocos dato’ implies a dialectal character, whereas the slightly erotic content fits well into the textual genre. A typology of the Latin and Gaulish spindle-whorls is also offered, together with a discussion of the other Celtiberian and Celtiberia-related texts.